2021
DOI: 10.1016/j.heliyon.2021.e06627
|View full text |Cite
|
Sign up to set email alerts
|

Innovative high-density polyethylene/waste glass powder composite with remarkable mechanical, thermal and recyclable properties for technical applications

Abstract: Several reinforcement materials are incorporated into a polymeric matrix to improve the mechanical properties and reduce the cost of the obtained composites. In this work, recycled high-density polyethylene/waste glass powder composites, compatibilized with maleic anhydride-grafted polyethylene, were prepared using a two-roll mill and compression molding techniques. Four levels of waste glass powder, 2, 10, 20 and 30% by weight, and five levels of the compatibilizer, polyethylene grafted with maleic anhydride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(36 reference statements)
2
3
0
Order By: Relevance
“…The tensile strengths of all the experimental groups (groups 2, 3, 4, 5, and 6) were smaller than that of the control group (group 1). Similar results were reported by Sadik et al (2021) and Karunanayake (2007). The tensile strengths of the experimental groups increased as the percentage of wood flour decreased and the percentage of glass flour increased.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The tensile strengths of all the experimental groups (groups 2, 3, 4, 5, and 6) were smaller than that of the control group (group 1). Similar results were reported by Sadik et al (2021) and Karunanayake (2007). The tensile strengths of the experimental groups increased as the percentage of wood flour decreased and the percentage of glass flour increased.…”
Section: Resultssupporting
confidence: 88%
“…The elongation at break values of all experimental groups (groups 2, 3, 4, 5, and 6) were smaller than that of the control group. Similar results related to plastic composites filled with glass flour were reported by Sadik et al (2021) and Karunanayake (2007). The difference was statistically significant (P < 0.001).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…High-density polyethylene (HDPE) is one of the polymers that has gained prominence as a multifaceted and environmentally friendly substance [ 17 ] within the industries of interior design, furniture manufacturing, and 3D printing. HDPE, known for its exceptional strength-to-density ratio, finds extensive utility throughout a diverse range of fields, encompassing innovative furniture design, sophisticated interior embellishments, and cutting-edge 3D-printing methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…They reach the conclusion that the fillers' particle size significantly influences the wear rate. Sadik et al [26] found that the addition of waste glass powder in the high-density polyethylene matrix enhances the tensile strength and modulus.…”
Section: Introductionmentioning
confidence: 99%